Reflection of Creative Values and Attitudes in The Surosowan Drum Corps Banten - Dandi Adhi Septian; Syahrul Syah Sinaga; Widodo Widodo (Ideas Publishing, 2023)
Character development is the main and crucial thing in the implementation of the formation of every culture and habit that is carried out in a group and environment seeing the activities of adolescents that need to be directed so as not to lead to negative actions. The purpose of this research is to provide an understanding of character values in the development of musical activities as a guideline that supports the development of the creative process in a group or individual. This research is supported by the qualitative method and uses a psychological approach as an analysis of the creativity of students. The findings in this study are about the values contained in Surosowan Drum Corps Banten as a support for the creativity of members and the community, as well as a reflection of that value which is poured through creative attitudes and behaviors.